PENYUSUNAN LAPORAN KEUANGAN TERKOMPUTERISASI PADA PONDOK PESANTREN MA’ARIFUL ULUM - Purnama Sari; Dewata, Evada; Kadarwati, Sari; Wilianto, Haris; Jauhari, Hadi (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2023)
This service aims to assist the Ma'ariful Ulum Islamic Boarding School in preparing computerized financial reports in accordance with ISAK 35. This Islamic boarding school has not prepared financial reports according to ISAK 35 due to lack of understanding in the field of accounting regarding applicable accounting standards. Data collection was done by interviewing techniques (interviews) and observations on the financial data recording of the Ma'ariful Ulum Islamic Boarding School. The data used are primary data in the form of interviews with the treasurer of the lodge and secondary data in the form of financial data consisting of cash income and expenditure in 2021. The results of this service are the preparation of computerized financial reports using Microsoft Excel consisting of Statements of Financial Position, Comprehensive Income Statements , Statement of Changes in Net Assets, Statement of Cash Flows, and Notes to Financial Statements. This service is considered very useful in terms of preparing financial reports quickly and accurately. In addition, this service is expected to run well and be used in the future. Keywords: Financial Statement, ISAK 35, Computerized